2000
DOI: 10.1021/ja003216+
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin Nonaketide Synthase Catalyzes an Intramolecular Diels−Alder Reaction of a Substrate Analogue

Abstract: The fungal metabolite lovastatin (1) 1 and its derivatives are cholesterol-lowering drugs that act as potent inhibitors of (3S)hydroxy-3-methylglutaryl-coenzyme A reductase. 2 Although 1 and compactin 3 have attracted attention from synthetic chemists, 4 these drugs and some analogues (e.g., simvastatin, pravastatin) which are used in humans are manufactured by fermentation, either directly or with subsequent chemical or microbial modification. Studies on the biosynthesis of 1 in Aspergillus terreus indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
236
1
10

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(249 citation statements)
references
References 27 publications
2
236
1
10
Order By: Relevance
“…Although putative enzymes for unimolecular [4+2] cycloadditions have been reported (1)(2)(3)(4), no naturally occurring enzyme is known to catalyze a bimolecular Diels-Alder reaction (5,6). The generation of artificial Diels-Alderases has therefore been a longstanding and alluring goal for protein engineers.…”
mentioning
confidence: 99%
“…Although putative enzymes for unimolecular [4+2] cycloadditions have been reported (1)(2)(3)(4), no naturally occurring enzyme is known to catalyze a bimolecular Diels-Alder reaction (5,6). The generation of artificial Diels-Alderases has therefore been a longstanding and alluring goal for protein engineers.…”
mentioning
confidence: 99%
“…Having served its purpose of controlling the atropdiastereoselectivity during the macrocyclization, the benzylic silyloxy group of 41 was removed under ionic hydrogenation conditions using trifluoroacetic acid and Et 3 SiH, affording 44 in 58% yield as a single atropisomer (Scheme 6). Removal of the TBS group generated 45 in 87% yield.…”
Section: Application Of Ene-yne Metathesismentioning
confidence: 99%
“…One is the lovastatin nonaketide synthase (LNKS), credited with producing lovastain's decalin core structure via a DielsAlder reaction, which was originally reported by Hutchinson and Vederas et al (Scheme 1b). 6,7) Although LNKS appears capable of biosynthesizing dihydromonacolin L via an endo Diels-Alder reaction, in vitro assays revealed that such biosynthesis would require an extra enzyme, LovC. Hence, no study has unambiguously demonstrated the ability of LNKS to catalyze a Diels-Alder reaction as a single-enzymatic reaction.…”
mentioning
confidence: 99%